2021
DOI: 10.3389/fped.2021.713447
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Molecular Tests for Guiding Therapeutic Decisions in Bloodstream Staphylococcal Infections: A Meta-Analysis

Abstract: Background: Treatment of bloodstream staphylococcal infections (BSI) necessitates the prompt initiation of appropriate antimicrobial agents and the rapid de-escalation of excessive broad-spectrum coverage to reduce the risk of mortality. We, therefore, aimed to demonstrate the diagnostic accuracy of nucleic acid amplification tests (NAAT) for the identification of methicillin-resistant S. aureus (MRSA) and methicillin-sensitive S. aureus (MSSA) in clinically suspected patients.Methods: Until November 23, 2020,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…Since it gives fast results and can identify dead microbes, we suggest utilizing NAAT in principle to diagnose staphylococcal BJI. In comparison to previously published systematic reviews, we found that the metaanalysis by Chen et al reported on the greater diagnostic value of NAAT for staphylococcal strains in LRT specimens (22) and blood specimens (23), which is consistent with the findings of this study. However, these reviews focused solely on the detection of MSSA or MRSA in fluids other than osteoarticular samples.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Since it gives fast results and can identify dead microbes, we suggest utilizing NAAT in principle to diagnose staphylococcal BJI. In comparison to previously published systematic reviews, we found that the metaanalysis by Chen et al reported on the greater diagnostic value of NAAT for staphylococcal strains in LRT specimens (22) and blood specimens (23), which is consistent with the findings of this study. However, these reviews focused solely on the detection of MSSA or MRSA in fluids other than osteoarticular samples.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, a few studies showed that NAAT was accurate in the diagnosis of staphylococcal pneumonia and pediatric sepsis ( 22 , 23 ); however, to the best of our knowledge, there is no published information on the functioning of the NAAT test for the identification of pathogens in BJI. NAAT, which usually have a faster reaction time and are unaffected by antibiotic exposure, may assist in the development of an etiological diagnosis to help guide patient treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Applicability concern in the patients’ selection domain was not a concern as all publications used samples from patients with possible infections, signaling a low risk of bias. Regarding index tests, all studies did not report about blinding of index tests except for three studies [ 65 67 ]; therefore, the risk of bias in the index test domain was considered unclear. The index test's applicability for all studies was considered unclear since there is not a globally accepted test methodology.…”
Section: Resultsmentioning
confidence: 99%
“…This may alter the patient’s microbiome leading to opportunistic infections, subject the patient to drug-related toxicity, and increase the cost of hospitalization. In addition, improper antibiotic use can select for resistant strains [ 28 , 51 ]. Using the developed MBDLFA on DNA extracted from positive blood cultures will also save the time required for traditional testing of MRSA and vancomycin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real-time PCR helps better interpret positive results, as the low abundance of bacteria usually characterizes contamination [ 28 ]. It is always a good practice to make parallel use of blood culture as the gold-standard method for diagnosis of bacteremia with PCR-based assays [ 51 ]. This will allow for the rapid detection of bacteremia with a high blood bacterial load and commencement of proper treatment within the first 2 h of sampling.…”
Section: Discussionmentioning
confidence: 99%